Coumarin-1,2,3-triazole hybrids as leading-edge anticancer agents - Mishra, Krishna N.; Upadhyay, Harish C. (Frontiers in Drug Discovery, 2022)
Cancer is one of the most feared and dreaded diseases across the world. In clinical practice, a variety of anticancer agents of natural, semi-synthetic and synthetic origin exist, but they suffer from side effects and drug resistance, so they are insufficient to combat the disease. Coumarins are bicyclic benzene-pyrone-fused phytomolecules with a wide range of biological effects, including powerful anticancer activity on numerous cell lines. Additionally, they serve as an adaptable synthetic scaffold and research hub for medicinal chemists. On the other hand, triazoles are nitrogen-containing heterocycles having remarkable pharmacological effects including anticancer activities. Due to a better compatibility with the human metabolic system, the synthesis of nature inspired hybrid compounds as anticancer agents for a wide range of activity and fewer side effects is at the forefront of current research. In the last decade, huge research has been published on coumarin-1,2,3-triazole hybrids showing potent anticancer activities on various types of cancer. This review offers a recent, thorough literature compilation of contemporary research on the development of hybrid compounds based on coumarin-1,2,3-triazoles as potential anticancer leads throughout the previous 10 years.